Scratch Area Effect in Coating to Protection Current Needing in ICCP System for AISI 1045 Steel in Sea Water Environment - Dewanti Dewanti; Tubagus Noor Rohmannudin; Sigit Tri Wicaksono (IPTEK Journal of Proceedings Series, 2014)
Every metal always going back to its oxide form. Steel which are oxidized having lower quality than steel which are not. Oxidizing steel will going faster if it is placed in corrosive environment. Sea water is one of the environment that support the oxidizing process. Coats are using to protect the steel in sea water. But sometimes there is some failure in coating process so the coat will have scratch damage area. The objective of this experiment is to know how much current needed to protect AISI 1045 steel which have been coated with polyethylene and given scratch area with shape variations, in sea water environment. This experiments is the continuation from the past experiences which is using sacrifice anode, on the other hand, this experiences using Impressed Current Cathodic Protection. Data which are taken from this experiment is the differentiation of potential that measured with electrode reference Cu/CuSO4, and the current measured by avometer. With ICCP system, we know that the corrosion rate in rectangular-shape scratch is faster than circle-shape scratch, and the larger the area of scratch, the larger current needed to protect the coated steel.